When fetal hydronephrosis is suspected antenatally—a qualitative study. Issue 1 (December 2015) - Oscarsson, Marie; Gottvall, Tomas; Swahnberg, Katarina
Abstract Background The information about fetal malformation findings during the ultrasound examination often comes unexpectedly, and the women and their partners may not necessarily receive any conclusive statement on the prognosis. A finding such as fetal hydronephrosis range from being a soft markers or mild anomaly, to a serious condition associated with neonatal morbidity and mortality. The aim of this study was to explore women's reactions to the discovery of fetal hydronephrosis in the context of uncertainty regarding the prognosis. Methods Ten women were interviewed and the interviews were conducted six to twelve months after the women gave birth. They had experience of suspected fetal hydronephrosis in gestational week 18–20. The interviews were recorded, transcribed verbatim and analysed using constant comparative analysis. Results The core category, 'Going through crisis by knowing that you are doing the right thing' illustrates the meaning of women's reactions and feelings. It illuminates the four categories: 'When the unexpected happens '– on the one hand, women had positive views that the suspicious malformation could be discovered; however, on the other hand, women questioned the screening.'To live in suspense during pregnancy' – the suspicious malformation caused anxiety and was a stressful situation.'Difficulties in understanding information' – the women thought they had limited knowledge and had difficulties in understanding the information. 'Suppress feelings and hope for the best' – the women tried to postpone the problem and thought they should deal with it after delivery. Conclusions Women are worried irrespective of suspicious or severe malformations, and in need of information and counselling tailored to their individual needs. Other sources of support could be: written information, links to reliable sources on the Internet and possibilities for ongoing follow-ups.